Experimental investigation on the influence of a single structural plane on rockburst. (February 2023) - Cheng, Tai; He, Manchao; Li, Hongru; Liu, Dongqiao; Qiao, Yafei; Hu, Jie
Graphical abstract: Highlights: The initial crack affects the location and intensity of the rockburst. Three mechanisms dominate the effects of the pre-existing crack on rockburst. Four different rockburst evolution modes are proposed for the tunnel. Abstract: The structural planes adjacent to the tunnel have a significant effect on rockburst, which has become an important engineering issue. To investigate the influence of such a rigid structural plane on rockburst, four different types of block specimens containing a through circular hole are designed with a prefabricated unfilled crack. A series of biaxial compression tests are then performed to simulate the rockburst process, followed by a detailed analysis of the strength characteristics, the strain field, the rockburst evolution process, and the microscopic characteristics of fracture surfaces. A prefabricated unfilled crack causes a decrease of the initial damage stress and the overall strength of block specimen, the earlier occurrence of rockburst but a decrease of initial rockburst intensity. Compared with the exposed crack, the non-exposed crack facilitates the occurrence of the rockburst more. Three mechanisms are proposed to explain these effects, including (i) the local stress concentration that alters the location of initial damage and the following crack propagation pattern, further affecting the location and scope of rockburst; (ii) the weakening effect that promotes rockburst evolution and inhibits rockburst intensity; and (iii) the sliding-induced secondary rockburst that contributes with significant energy release once the pre-existing crack is compacted. In light of the experimental observations, four different rockburst evolution modes are summarized to help to understand the rockburst in practical tunnels, and some engineering measures are recommended for the controlling and prevention of rockburst.